2017
DOI: 10.12688/wellcomeopenres.12620.1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Major Depression Inventory among young people living in Coastal Kenya

Abstract: The lack of reliable, valid and adequately standardized Background measures of mental illnesses in sub-Saharan Africa is a key challenge for epidemiological studies on mental health. We evaluated the psychometric properties and feasibility of using a computerized version of the Major Depression Inventory (MDI) in an epidemiological study in rural Kenya.: We surveyed 1496 participants aged 13-24 years in Kilifi County, on Methods the Kenyan coast. The MDI was administered using a computer-assisted system, avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…This study’s findings from non-psychometric evaluation of the HRB questionnaire delivered via ACASI highlight the feasibility of using ACASI for collecting sensitive data such as information on HRB among adolescents in this rural low resource setting. In support of our findings, ACASI has previously been used among the adolescent population in Kilifi [ 52 ], as well as among an older age-group within the Kenyan setting [ 53 , 54 ]. Overall, these studies have found the ACASI to improve quality of response to sensitive questions, to decrease socially desirable responses, and has also suitably been used for collecting data among participants with low formal education [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 88%
“…This study’s findings from non-psychometric evaluation of the HRB questionnaire delivered via ACASI highlight the feasibility of using ACASI for collecting sensitive data such as information on HRB among adolescents in this rural low resource setting. In support of our findings, ACASI has previously been used among the adolescent population in Kilifi [ 52 ], as well as among an older age-group within the Kenyan setting [ 53 , 54 ]. Overall, these studies have found the ACASI to improve quality of response to sensitive questions, to decrease socially desirable responses, and has also suitably been used for collecting data among participants with low formal education [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 88%
“…Participants’ depressive symptoms over the past two weeks were assessed using the major depression inventory (MDI); which has been found reliable (Cronbach’s alpha = 0.83) and valid (Loevinger’s H coefficient for MDI’s 10 items was 0.38 confirming a unidimensional structure) to use among adolescents in this setting [ 51 ]. Both total raw scores from MDI and diagnostic classifications (i.e.…”
Section: Methodsmentioning
confidence: 99%
“… 38 This measure, adapted to Swahili, yielded reliable psychometric properties among young adults in Kilifi. 39 …”
Section: Methodsmentioning
confidence: 99%